PENGARUH PELATIHAN TANGGAP TUBERKULOSIS DAN PENDAMPINGAN MINUM OBAT TERHADAP PENGETAHUAN KADER KESEHATAN DESA DI KECAMATAN BLUTO - Rahem, Abdul; Wijaya, I Nyoman; Ifadotunnikmah, Farida; Rahmadi, Mahardian; Achmad, Gusti Noorrizka Veronika; Athiyah, Umi; Yuda, Ana; Zulkarnain, Bambang Subakti; Nugraheni, Gesnita; Ardianto, Chrismawan; Sumarno, Sumarno; Aryani, Toetik; Budiatin, Aniek Setiya; Hermansyah, Andi; Sulistyarini, Arie; Priyandani, Yuni; Sukorini, Anila Impian (Jurnal Insan Farmasi Indonesia, 2024)
Tuberculosis (TB) is one of the leading causes of death from infectious diseases worldwide. Indonesia ranks as the country with the second-highest number of TB cases after India. TB awareness training and medication adherence support for village health cadres are strategic steps to enhance their capacity in supporting TB treatment. This study aims to analyze the impact of TB awareness training and medication adherence support on improving the knowledge of village health cadres. A pre-experimental study with a pretest-posttest design was conducted involving 50 village health cadres in Bluto Subdistrict, Sumenep Regency. Data were collected using questionnaires administered before and after the training. Analysis was performed using the Mann-Whitney test. There was a significant increase in the knowledge scores of village health cadres regarding TB (pretest: 3.50 ± 1.65; posttest: 5.64 ± 2.70; p<0.05) and anti-TB drug side effects (pretest: 7.66 ± 4.07; posttest: 15.04 ± 3.11; p<0.05). The training also successfully enhanced the cadres' understanding of TB symptoms, prevention, and treatment, including drug side effects. TB awareness training and medication adherence support significantly improved the knowledge of village health cadres, making them more competent in supporting TB control efforts at the community level.